2004
DOI: 10.1021/om049756n
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Catalysts with Scorpionate Ligands for Olefin Polymerization

Abstract: The catalyst systems composed of hydrotris-(pyrazolyl)borate (Tp) manganese and coactivators showed good activity for ethylene polymerization and ethylene-R-olefin lymerizations goes up to 1.6 × 10 7 g mol(cat) -1 h -1 , giving ethylene-1-butene copolymer with a narrow molecular weight distribution (M w /M n ) 1.8) and a high melting point (120°C). This system is also active toward propylene and gives isotactic polypropylene with a triad mm fraction of 0.905.Since the discovery of group 4 metallocene single-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…In all cases, the ethylene polymerization activity of a and b activated by TIBA/TB(II) was greater than that activated by MMAO(I). This tendency was the same as the related manganese(II) chloro complex c with the anionic borate ligand [16]. In particular, when MMAO was used as an activator, a negligible weight of polymer was obtained ( Table 1, entries 1 and 3).…”
Section: Ethylene Homopolymerization Behaviorsupporting
confidence: 61%
See 2 more Smart Citations
“…In all cases, the ethylene polymerization activity of a and b activated by TIBA/TB(II) was greater than that activated by MMAO(I). This tendency was the same as the related manganese(II) chloro complex c with the anionic borate ligand [16]. In particular, when MMAO was used as an activator, a negligible weight of polymer was obtained ( Table 1, entries 1 and 3).…”
Section: Ethylene Homopolymerization Behaviorsupporting
confidence: 61%
“…The sterically crowded tris(pyrazolyl)methane ligand L1 was synthesized by the reaction between 3,5-diisopropylpyrazole and CHCl 3 [16,18]. The reaction of L1 with 0.9 equiv.…”
Section: Structures Of Manganese(ii) Complexes a And Bmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed the manganese(II) based catalysts with N3 tripod hydrotris(pyrazolyl)borate ligands. We have reported that Mn II ‐based complexes, [Mn(L3)(X)] (X = Cl, Br, or NO 3 ; L3 – = hydrotris(3‐tertiary butyl‐5‐isopropyl‐1‐pyrazolyl)borate anion) showed to compete with the general metallocene catalyst systems, having relatively narrow molecular weight distribution ( M w / M n = 1.8),16 and [Mn(L1′)(X) 2 ] (X = Cl or Br; L1′ = tris(3,5‐diisopropyl‐1‐pyrazolyl)methane) displayed better 1‐hexene reactivity of ethylene/1‐hexene copolymerization than [Mn(L3)(X)] 17…”
Section: Introductionmentioning
confidence: 99%
“…Manganese compounds are frequently used as catalytic precursors in epoxidation of alkenes [19][20][21], oxidation of sulfides [22,23] and hydrocarbons [24,25] as well as various asymmetric reactions [26]. Recently, a few of manganese complexes have also been reported in olefin polymerization [27][28][29][30]. Therefore, the relevant complexes of manganese, cobalt and nickel would be interestingly investigated together.…”
Section: Introductionmentioning
confidence: 99%